THE FINANCIAL DEVELOPMENT, INSTITUTIONS, AND POVERTY REDUCTION: EMPIRICAL EVIDENCE FROM SOUTH ASIAN COUNTRIES - Labony, Shamim Ara; Haque, Md. Shariful; Rahman, Farzana; Shahabuddin, A. M.; Sultana, Tania (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
Fighting poverty is one of the most critical targets of development plans and initiatives. In the pursuit of lasting growth, emerging nations now face the most challenging issue of eliminating poverty, which remains one of the most significant challenges addressing humanity nowadays. The study explores the relationships between the institutional quality, financial development, and poverty-fighting initiatives of South Asian states. It goes beyond the potential bias in earlier studies caused by omitting variables by considering the impact of the interaction between the financial sector and institutional framework. The fixed effects models with STATA15 are employed in this study from 2000 to 2019. This study's analysis uses panel data and secondary sources to conduct the inquiry with a sample of 7 South Asian economies such as Bangladesh, Bhutan, India, the Maldives, Nepal, Pakistan, and Sri Lanka. This comprehensive compilation of annual data was done with consultation from the International Monetary Fund (IMF) and the World Bank Development Indicators (WDI). The study results show that a 1% increase in financial development is associated with a 39.88% decrease in poverty, which is statistically significant and favourable. It also reveals that institutional quality plays a vital role in poverty reduction in South Asia, with a 1% increase in institutional quality leading to a 2.61% increase in poverty. Besides, a 1% increase in GDP per capita growth correlates with a 0.12% decrease in poverty. The study's findings provide significant insights into poverty reduction by considering the relationship between institutional challenges and financial development through a flexible, functional structure in South Asian countries. JEL Classification Codes: O16, I32, O53, C23.